Effects of different magnetic stimulation paradigms on post-stroke upper limb function: a randomized controlled trial - Xu, Li; Luo, Hong; Huang, Lin; Chen, Shuang; Liu, Huifang; Cui, Wei (Frontiers in Neurology, 2025)
BackgroundCurrent evidence suggests that repetitive transcranial magnetic stimulation (rTMS), repetitive peripheral magnetic stimulation (rPMS), and their combined application can all enhance upper limb functional recovery after stroke. However, their comparative therapeutic profiles, including relative advantages and limitations, have not been systematically characterized.ObjectivesTo compare rTMS, rPMS, and combined protocols for post-stroke upper limb recovery, analyzing both functional outcomes and neural mechanisms to guide therapeutic selection.MethodsFifty-one stroke patients were randomly divided into an rTMS group, rPMS group, or a combined group. Before and after 3 weeks of intervention, all patients were assessed with the Fugl-Meyer assessment for the upper limb (FMA-UL), the Thumb Localizing Test (TLT), modified Barthel index (MBI), and resting-state functional magnetic resonance imaging (rs-fMRI).ResultsThe ΔFMA-UL and ΔMBI scores of the combined group were significantly better than the rTMS group and rPMS group. The ΔTLT scores of the combined group and rPMS were significantly better than the rTMS group, but there was no statistically significant difference in ΔTLT scores between rPMS and the combined group. Compared to the rTMS group, the rPMS group showed increased amplitude of low-frequency fluctuation (ALFF) in the ipsilesional superior frontal gyrus, cerebellum_8 area, and contralesional cerebellum_crus1; the combined group showed increased ALFF in the ipsilesional cerebellum_8 area, superior medial frontal gyrus, and contralesional cerebellum_crus2 area. Compared with the rPMS group, the combined group showed increased ALFF in the ipsilesional paracentral lobule, supplementary motor area, precentral gyrus, and superior medial frontal gyrus.ConclusionCompared with rTMS, rPMS has certain advantages in improving proprioception after stroke, and combination therapy improves both motor and proprioception. Therefore, combination therapy is recommended to better promote the recovery of brain and limb function.Clinical trial registrationhttp://chictr.org.cn, Identifier ChiCTR2200065871.